Determination of inequable fate and toxicity of Ag nanoparticles in a Phanerochaete chrysosporium biofilm system through different sulfide sources. Issue 5 (26th July 2016) - Guo, Zhi; Chen, Guiqiu; Zeng, Guangming; Liang, Jie; Huang, Binbin; Xiao, Zhihua; Yi, Feng; Huang, Zhenzhen; He, Kai
Abstract : Cysteine and Na2 S induced different distributions and toxicities of AgNP in biofilms. Abstract : Nanomaterials, especially silver nanoparticles (AgNP), are widely used in consumer products, yet their environmental fate and risk to biological wastewater treatment systems is poorly understood. In this study, we investigated the distribution of AgNP coated with polyvinylpyrrolidone (PVP) and citrate (Cit) (PVP-AgNP and Cit-AgNP, respectively) in a Phanerochaete chrysosporium ( P. chrysosporium ) biofilm microcosm, with either the organic sulfide, cysteine, or the inorganic sulfide, Na2 S, present in the test environment. Both types of AgNP tested easily penetrated the P. chrysosporium biofilm and remained mostly in the bottom layer (1.6–2.0 cm) when cysteine was present. In contrast, both types of AgNP remained in the surface layer (0–0.4 cm) in an aggregated form in the presence of Na2 S. An obvious particle-specific toxicity to the film was observed, despite the inhibited Ag + release in cysteine-abundant surroundings. In the presence of Na2 S, the toxicity of both types of AgNP was completely inhibited. In conclusion, this work indicates that sulfide-induced particle stability (cysteine has no effect on Cit-AgNP and induced a smaller size of PVP-AgNP, and Na2 S caused both types of AgNP to aggregate) was crucial to AgNP transfer and toxicity in biofilms.